Innovation of Diagnosis and Treatment for Pancreatic Cancer - Yamaue, Hiroki (Springer Singapore : Imprint: Springer, 2017)
This collection of chapters describes in detail the latest insights into the evaluation of resectability and neoadjuvant therapy to pancreaticoduodenectomy and distal pancreatectomy for pancreatic cancer. Shedding light on immunotherapy and gene therapy, this volume comprehensively covers treatments and procedures for the disease, allowing surgeons and trainees to gain an overview and explore innovative treatments. It also provides information on various cases using tools such as endoscopic ultrasound, MDCT, PET for diagnosis and laparoscopy and robotic resection methods. Edited and authored by pioneering professionals, Diagnosis and Treatment for Pancreatic Cancer is a valuable resource for gastroenterologists, medical oncologists, surgical oncologist and general surgeons interested in treatment of pancreatic cancer care.